Legal Consequences of Official Appointment of Non-Government Civil Servants Head District: Case of Salahutu District, Central Maluku Regency - Lainsamputty, Natanel (Indonesian Journal of Advocacy and Legal Services, 2020)
The administration of the Negeri government in Salahutu Sub-district of Maluku District was in the middle of a government vacuum, so the provision of positions carried out in practice appointed the acting head of the Negeri government who was not a civil servant from the district / city environment. This issue is clearly in conflict with applicable laws and regulations. So this research aims to analyze the appointment of the acting head of the Negeri government that is not of civil servants and how the legal consequences. The concept of appointing an official to fill the government vacancy in the village or what is called by another name, is to carry out government functions related to public services and development, so that the civil servants are competent.